2020
DOI: 10.1002/advs.201903164
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Promotes Genetic and Functional Modifications of Therapeutic T Cells Against Cancer

Abstract: Growing experience with engineered chimeric antigen receptor (CAR)‐T cells has revealed some of the challenges associated with developing patient‐specific therapy. The promising clinical results obtained with CAR‐T therapy nevertheless demonstrate the urgency of advancements to promote and expand its uses. There is indeed a need to devise novel methods to generate potent CARs, and to confer them and track their anti‐tumor efficacy in CAR‐T therapy. A potentially effective approach to improve the efficacy of CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 149 publications
0
19
0
Order By: Relevance
“…[ 13 ] There have been several on‐switch strategies to improve efficacy and safety of CAR‐T therapy. [ 22 ] For example, Stepanov et al. [ 20 ] designed a barstar‐based CAR.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] There have been several on‐switch strategies to improve efficacy and safety of CAR‐T therapy. [ 22 ] For example, Stepanov et al. [ 20 ] designed a barstar‐based CAR.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages offered by nanotechnology open the possibility to implement nanoformulations in the CAR cell technology. Among many other options, the transfection competency of CARs encoding mRNA or DNA by polymeric nanoparticles showed a high compatibility with T and NK cells [ 204 , 205 ]. Compared to electroporation, the use of mRNA-carrying nanoparticles has shown a higher viability and higher expansion rates of T cells [ 206 , 207 ].…”
Section: Car Transfer Methodology Into Nk Cellsmentioning
confidence: 99%
“…Therefore, there is an urgent need to improve current cancer immunotherapies, and Ahmed et al found that NP-based methods can improve their ability to enhance T cell activation on tumor cells and improve their antitumor efficacy with minimal toxicity [198]. Effective control of the release of immune agonists or adjuvants is an important way to avoid the attacks on normal tissues and organs caused by excessive immune activation.…”
Section: Immunotherapy Based On Polymer Nanocarriersmentioning
confidence: 99%